2017
DOI: 10.1016/j.stemcr.2017.03.011
|View full text |Cite
|
Sign up to set email alerts
|

High-Throughput and Cost-Effective Characterization of Induced Pluripotent Stem Cells

Abstract: SummaryReprogramming somatic cells to induced pluripotent stem cells (iPSCs) offers the possibility of studying the molecular mechanisms underlying human diseases in cell types difficult to extract from living patients, such as neurons and cardiomyocytes. To date, studies have been published that use small panels of iPSC-derived cell lines to study monogenic diseases. However, to study complex diseases, where the genetic variation underlying the disorder is unknown, a sizable number of patient-specific iPSC li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
52
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(54 citation statements)
references
References 34 publications
1
52
1
Order By: Relevance
“…Overall, genomic integrity for these low-passage lines was high with almost half of the iPSCs in the iPSCORE resource showing no detectable abnormalities, and ∼90% showing less than 2 Mb of cumulative CNV coverage (in bp). It is important to note that genotype array assays are limited to the extent that they are unable to detect balanced chromosomal translocations or abnormalities occurring at a frequency lower than 20% (D'Antonio et al., 2017 [this issue of Stem Cell Reports ]); however, previous studies using genotype arrays have found higher ratios and frequencies of abnormalities in iPSCs (International Stem Cell et al., 2011, Laurent et al., 2011, Taapken et al., 2011) than we report, suggesting that a systematic approach to iPSC generation can result in significantly fewer abnormalities. We also used RNA-seq data to validate the quality of the iPSCORE lines by comparing them with publicly available RNA-seq data for stem cells previously shown to be pluripotent and performed pluripotency estimation using PluriTest-RNAseq.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, genomic integrity for these low-passage lines was high with almost half of the iPSCs in the iPSCORE resource showing no detectable abnormalities, and ∼90% showing less than 2 Mb of cumulative CNV coverage (in bp). It is important to note that genotype array assays are limited to the extent that they are unable to detect balanced chromosomal translocations or abnormalities occurring at a frequency lower than 20% (D'Antonio et al., 2017 [this issue of Stem Cell Reports ]); however, previous studies using genotype arrays have found higher ratios and frequencies of abnormalities in iPSCs (International Stem Cell et al., 2011, Laurent et al., 2011, Taapken et al., 2011) than we report, suggesting that a systematic approach to iPSC generation can result in significantly fewer abnormalities. We also used RNA-seq data to validate the quality of the iPSCORE lines by comparing them with publicly available RNA-seq data for stem cells previously shown to be pluripotent and performed pluripotency estimation using PluriTest-RNAseq.…”
Section: Discussionmentioning
confidence: 99%
“…Stem cell derivation and quality control options including the best ways to assess genomic integrity have been reviewed many times, so I focus here on neural differentiation and issues for neurodevelopmental disease research. Once iPSCs have been made and carefully validated, one can begin to think about the optimal way to make neuron‐like cells.…”
Section: Identification and Selection Of Neural Populationsmentioning
confidence: 99%
“…It is reasonable to think that there is an urgent need to find a cost-effective manner to overcome this hurdle, which would definitely ease the iPSCs translation to the clinics. In this regard, although autologous therapies can be particularly attractive in terms of personalized treatments [75], the current cost of such therapies would indeed be prohibitive and definitely time-consuming [76]. That is why allogeneic therapies may be a good alternative, as they are more economical and could reach a wider number of patients.…”
Section: Economic Issuesmentioning
confidence: 99%